Synergy in a Team – Quality Analysis of Conditions - Jasińska, Monika (Management and Administration Journal, 2019)
Synergy is a powerful tool that emerges when the social potential is improved and high activity is achieved. This is a feature of well-functioning and continuously learning teams. The aim of the study is to examine circumstances that may favour synergy in team work. Teams functioning in a company that is typical for a learning organisation were selected to conduct analysis in the case study. In order to collect the data, the author applied grounded theory and surveys along with descriptive and analytical methods. The study proved that team synergy conditions are the quality of cooperative relations, entrepreneurial potential and measurable effects of joint action.